The Added Value of Geographical Information Systems in Public and Environmental Health
XXIX, 358 p. 54 illus.
Keywords: Health for all by the year 2000 is the blueprint for change agreed to by the Member States of the World Health Organization. In Europe, this blueprint is built on 38 regional targets, many of which have the underlying aim of uncovering new knowledge and of using existing knowledge more effectively. The targets related to a healthy environment have the ultimate goals of safeguarding human health against environmental hazards, and of enhancing the quality of life by providing clean and safe water, air, food, and working and living conditions. Allied to these goals is the need to reduce the sense of jeopardy that many people feel about what they perceive as 'the risks of everyday life'. These goals are an integral part of the European Charter on Environment and Health, adopted by 29 European Member States and the Commission of the European Communities in December 1989. The Charter stresses the shared responsibility of everyone to protect the environment, to be given adequate and accurateinformation, and to be involved in decision-making. It outUnes the principles for public policy as well as what needs to be done to transform them into action. In this, strong information systems have a vital role to play by helping to monitor the effectiveness of measures taken, of trends analysed, of priorities set and of decisions made.